Analisis Faktor Yang Mempengaruhi Kinerja Sistem Informasi Akuntansi - Saputro, Tegar Nur; Kusumawati, Eny (Universitas Syiah Kuala, 2023)
Accounting Information System (AIS) is a collection of resources designed to process, process, and analyze financial data into information that can be used by internal and external stakeholders of the company. This study aims to analyze the effect of user skills, training and education programs, support from top management, participation of AIS users, and sophistication of information technology on information system performance. This research was conducted at BUMDs in Jepara district, Central Java province. The sampling technique used purposive sampling which obtained 103 respondents. The results of the study provide empirical evidence that user ability affects the performance of accounting information systems, while training and education programs, top management support, user participation and information technology sophistication have no effect on the performance of accounting information systems.